Basal testosterone, leadership and dominance: A field study and meta-analysis. (October 2016) - van der Meij, Leander; Schaveling, Jaap; van Vugt, Mark
Highlights: We investigated testosterone and leadership in a field study and meta-analysis. Basal testosterone was related to authoritarian leadership only in non-managers. Basal testosterone was not different between managers and non-managers. The meta-analysis also showed that basal testosterone was unrelated to leadership position. Abstract: This article examines the role of basal testosterone as a potential biological marker of leadership and hierarchy in the workplace. First, we report the result of a study with a sample of male employees from different corporate organizations in the Netherlands ( n = 125). Results showed that employees with higher basal testosterone levels reported a more authoritarian leadership style, but this relationship was absent among those who currently held a real management position (i.e., they had at least one subordinate). Furthermore, basal testosterone levels were not different between managers and non-managers, and testosterone was not associated with various indicators of status and hierarchy such as number of subordinates, income, and position in the organizational hierarchy. In our meta-analysis (second study), we showed that basal testosterone levels were not associated with leadership in men nor in women (9 studies, n = 1103). Taken together, our findings show that basal testosterone is not associated with having a leadership position in the corporate world or related to leadership styles in leaders. We suggest that basal testosterone could play a role in acquiring leadership positions through dominant and authoritarian behavior.